Aqueous Electrochemical Reduction of Carbon Dioxide and Carbon Monoxide into Methanol with Cobalt Phthalocyanine. Issue 45 (25th September 2019) - Boutin, Etienne; Wang, Min; Lin, John C.; Mesnage, Matthieu; Mendoza, Daniela; Lassalle‐Kaiser, Benedikt; Hahn, Christopher; Jaramillo, Thomas F.; Robert, Marc
Abstract: Conversion of CO2 into valuable molecules is a field of intensive investigation with the aim of developing scalable technologies for making fuels using renewable energy sources. While electrochemical reduction into CO and formate are approaching industrial maturity, a current challenge is obtaining more reduced products like methanol. However, literature on the matter is scarce, and even more for the use of molecular catalysts. Here, we demonstrate that cobalt phthalocyanine, a well‐known catalyst for the electrochemical conversion of CO2 to CO, can also catalyze the reaction from CO2 or CO to methanol in aqueous electrolytes at ambient conditions of temperature and pressure. The studies identify formaldehyde as a key intermediate and an unexpected pH effect on selectivity. This paves the way for establishing a sequential process where CO2 is first converted to CO which is subsequently used as a reactant to produce methanol. Under ideal conditions, the reaction shows a global Faradaic efficiency of 19.5 % and chemical selectivity of 7.5 %. Abstract : Turning the wheel even further : Cobalt phthalocyanine, a well‐known catalyst for the electrochemical reduction of CO2 to CO, is reported to further reduce carbon monoxide into methanol in aqueous electrolytes at ambient conditions of temperature and pressure. Formaldehyde is an intermediate on the reaction pathway. Under optimized conditions, CO2 can be converted into methanol in two electrochemical steps with a 19.5 % global Faradaic efficiency.